PENGARUH TATA KELOLA PERUSAHAAN TERHADAP EFISIENSI MODAL INTELEKTUAL (Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Tahun 2016-2020) - Christina Adriani Hapsari; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to empirically investigate the relationship between corporate governance, such as board independence, board size, block shareholders, audit committee size and the frequency of audit committee meetings on the efficiency of intellectual capital in financial sector companies in Indonesia. This study uses control variables, namely firm age, firm size, leverage and ROE (return on total equity). The population in this study consisted of financial companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. The sample was selected based on the purposive sampling method. The total sample obtained is 305 companies for five consecutive years.This study was analyzed using the multiple linear regression method. The results of this study indicate that board independence, board size, block shareholder and the frequency of audit committee meetings have a significant positive effect on intellectual capital efficiency, while the size of the audit committee has no significant effect on intellectual capital efficiency.